ASSESSMENT OF DEPRESSION IN HEADACHE PATIENTS: INFLUENCE OF SECONDARY VARIABLES - B, Gururaj; Souza L, D (International Journal of Psychosocial Rehabilitation, 2021)
This study is an attempt at assessing the levels of depression in headache patients. A total number of 105 patients (50 M + 55 F) have been purposively selected for the study. Hamilton Rating Scale for Depression (1960) has been utilized to assess the depression in the sample. The results revealed that - Patients with psychogenic type of headache were found to have higher levels of depression and organic and migraine type of headache had the least depression. Gender did not have any influence on the depression level. Age of the patients did not have any influence on the depression level. Married patients had significantly higher levels of depression compared to unmarried and widow patients.